Legal Liability on Notary Negligence in Electronic Registration of Fiduciary Guarantee - Laura Chrismetin; Gunarto Gunarto (Sultan Agung Notary Law Review, 2022)
This study aims to analyze and be able to find out about legal liability for notary negligence in registering fiduciary guarantees electronically. In the registration of online fiduciary guarantees, there is a big responsibility on the Notary because after completing filling in the data to continue the next access, the Notary is asked to approve in advance the statement that all data contained in the form is correct by marking the statement. The type of data in this legal research uses primary legal materials and secondary legal materials, as well as tertiary legal materials. Based on the results of research and discussion, Notaries in carrying out their duties, especially those related to making certificates, must be professional in accordance with applicable rules and notaries must be able to minimize mistakes at work due to the notary's carelessness can be called a practice mall and can be sued by the client as the responsibility of a profession carried by a notary.